Advisory Boards in Startups : Investigating the Roles of Advisory Boards in German Technology-Based Startups. - Weber, Eric (Springer Fachmedien Wiesbaden, 2016)
Annotation The author shows that advisory boards in technology-based startups have seven different roles and functions: control, advice, networking, signalling, capital provision, co-management, coordination. It is shown that venture capital investors try to influence the importance of these roles in favour of control, coordination and co-management. Contrary to this, the satisfaction of founders as well as advisory board members increases with a higher importance of advice, networking and signalling. This analysis provides both qualitative and quantitative empirical data on the usage of those boards in practice.
Keywords: New business enterprises.; Advisory boards -- Germany.; Germany.; elektronické knihy; electronic books